2020
DOI: 10.21203/rs.3.rs-68599/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potential diagnostic value of pleural fluid cytokines levels for tuberculous pleural effusion

Abstract: Background: Tuberculous pleural effusion (TPE) is one of the most common forms of extrapulmonary tuberculosis. Patients with tuberculous or malignant pleural effusions (MPE) frequently have similar clinical manifestations and pleural fluid profile. New biomarkers for the differential diagnosis of TPE are required. Objective: We sought to determine of whether cytokine profiles in the pleural effusion of patients were suitable as tools for the differential diagnosis of TPE. Methods: 30 patients with TPE, 30 pati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Then in M.tb infection, the various levels of cytokines contribute to determining outcomes of infection [11]. Studies found that cytokines of IL-1β, IL-6, IL-17, IL-31, IL-33, tumor necrosis factor-α (TNF-α) and IFN-γ, may contribute to more e cient diagnosis strategies in the management of tuberculous pleurisy [12][13][14][15][16]. But there was no synchronous comparison of the diagnostic value of each cytokine in tuberculous pleurisy.…”
Section: Introductionmentioning
confidence: 99%
“…Then in M.tb infection, the various levels of cytokines contribute to determining outcomes of infection [11]. Studies found that cytokines of IL-1β, IL-6, IL-17, IL-31, IL-33, tumor necrosis factor-α (TNF-α) and IFN-γ, may contribute to more e cient diagnosis strategies in the management of tuberculous pleurisy [12][13][14][15][16]. But there was no synchronous comparison of the diagnostic value of each cytokine in tuberculous pleurisy.…”
Section: Introductionmentioning
confidence: 99%